Regimes de violência: narrativas ao redor de um lugar "seguro" - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This dissertation is the result of a process of interlocution with several residents and workers of a place considered "safe" in Petropolis, neighborhood of Manaus. It intends to interpret senses, representations and social dispositions constructed by individuals from their daily experiences of violence. The research resorted to narratives about themselves, about the other and about the place as instruments of analysis for the reconstruction of sociological frames. The analysis allowed us to understand the formation of different regimes of violence in which respect emerges as a recurrent statement.
Keywords: Violência; Sociologia urbana; História de vida; Petrópolis (bairro de Manaus); CIÊNCIAS HUMANAS: SOCIOLOGIA